Pengaruh Harga Minyak Dunia dan Dow Jones Islamic Market Index (DJIM) terhadap Jakarta Islamic Index (JII) - Lubis, Zul Fahmi; Fadhila, Tri Inda; Syarvina, Wahyu (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The Jakarta Islamic Index (JII) is one of the indices on the Indonesia Stock Exchange (IDX). The index, which was launched on July 3, 2000, is intended to accommodate investors who wish to invest in the stock market in sharia-compliant stocks. As for the increase and decrease in stock prices, of course there are several indicators that influence it, one of which is macroeconomic factors. Macroeconomic factors are the factors that become the center of attention of investors, these factors are the occurrence of World Oil Prices, the Dow Jones Islamic Market Index, and the Jakarta Islamic Index. So these factors have the potential to increase profits or reduce risks. The aim of the research is to determine the effect of world oil prices and the Dow Jones Islamic Index (DJIM) on the Jakarta Islamic Index (JII). This research is a quantitative research using secondary data from the annual reports of related variables. The samples in this study were taken during the 2016-2020 period. The statistical test used in this study used the Eviews 10 program with quantitative analysis. The results of the study show that the first hypothesis, World Oil Prices have a positive and significant effect on the Jakarta Islamic Index. The second hypothesis, the Dow Jones Islamic Market Index has no effect on the Jakarta Islamic Index. The third hypothesis, simultaneously the two independent variables have a positive and significant effect on the Jakarta Islamic Index.